Multidrug-Resistant Cytomegalovirus Infection in a Patient with Granulomatosis with Polyangiitis during Immunosuppressive Treatment. Issue 2 (February 2020) - Piccirilli, Giulia; Chiereghin, Angela; Maritati, Martina; Turello, Gabriele; Felici, Silvia; Corte, Renato La; Gabrielli, Liliana; Contini, Carlo; Lazzarotto, Tiziana
Cytomegalovirus (CMV) infection is a major complication in immunocompromised patients, including those with autoimmune diseases. Here, we describe the first case of granulomatosis with polyangiitis treated with steroids and cyclophosphamide, complicated by a multid-rug-resistant (MDR) CMV infection in presence of weak antiviral cellular immunity. Since reports regarding CMV infection in rheumatological patients are rarely described and no guidelines on its management exist, the described case contributes to identify potential strategies to predict the risk of CMV disease and developing of MDR-CMV in these patients, through virological and immunological surveillance.